Pengolahan Sampah Menjadi Bahan Kerajinan Untuk Mengurangi Sampah di Masyarakat - Alvian Maranalom Siregar; Asima Tiara Agnesia Pasaribu; Dwidya Nuari; Meilinda Suriani Harefa (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2023)
One way to maintain environmental comfort is to prioritize and prioritize the cleanliness of the environment where you live through cleanliness, especially waste management (Khairunnisa et al., 2019; Wati et al., 2021). Waste management is an inseparable part of environmental cleanliness, because waste is basically thrown away or dumped into the environment by humans, so it can have a negative impact on the environment. (Gelbert, Prihanto, & Suprihatin, 2010). Through good waste management, we can improve environmental quality and public health and convert waste into resources (Khairunnisa et al., 2019; Suryani, 2014). Improper handling of waste problems can endanger public health aspects due to environmental pollution and aesthetic problems.